Fish Oil And/Or Probiotics Intervention in Overweight/Obese Pregnant Women and Overweight Risk in 24-Month-Old Children - Saros Lotta; Vahlberg Tero; Koivuniemi Ella; Houttu Noora; Niinikoski Harri; Tertti Kristiina; Laitinen Kirsi (Lippincott Williams & Wilkins, 2025)
​​​​​​​
Objectives:
To evaluate whether a fish oil and/or probiotics intervention in pregnant women with overweight or obesity would influence the tendency of their 24-month-old children to become overweight and alter their body fat percentage.
Methods:
Women (n = 439) were double-blindly randomized into 4 intervention groups: fish oil+placebo, probiotics+placebo, probiotics+fish oil, and placebo+placebo (fish oil: 1.9 g docosahexaenoic acid and 0.22 g eicosapentaenoic acid, probiotics: Lacticaseibacillus rhamnosus HN001 and Bifidobacterium animalis ssp. lactis 420, 1010 colony-forming units each). The intervention lasted from early pregnancy until 6 months postpartum. Children’s (n = 330) growth data (height, weight, head circumference), a secondary outcome of the trial, were evaluated at birth, 3, 6, 12, and 24 months of age and compared to Finnish growth charts. Body fat percentage was measured with air displacement plethysmography (24 months). Logistic regression and general linear models were used to analyze the data.
Results:
Probiotics+placebo [weight-for-height% adj. Odds ratio (OR) = 0.36, 95% confidence interval (CI) = 0.14–0.95] and probiotics+fish oil [weight-for-age standard deviation score (SD-score) adj. OR = 0.22, 95% CI = 0.07–0.71] associated with lower overweight odds in 24-month-old children compared to placebo+placebo. Results remained essentially the same, when probiotics’ main effect (combined probiotics+placebo and probiotics+fish oil) was estimated; that is, lower overweight odds (weight-for-height% adj. OR = 0.48, 95% CI = 0.25–0.95 and weight-for-age SD-score adj. OR = 0.42, 95% CI = 0.20–0.88) compared to non-probiotics. No fish oil main effect (combined fish oil+placebo and probiotics+fish oil) was seen. The intervention did not influence body fat percentage.
Conclusions:
The administration of probiotics solely and in combination with fish oil during pregnancy to women with overweight or obesity lowered the overweight odds of their 24-month-old children.